Self Disclosure Melalui Instagram Stories (Studi pada Pelajar SMA Negeri 1 Lubuk Pakam) - Purba, Paulina Windy Tiofani; Sahputra, Dedi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study aims to analyze the form and impact of self-disclosure carried out by students of SMA Negeri 1 Lubuk Pakam through the Instagram Stories feature. The approach used was qualitative descriptive, with data collection techniques in the form of non-participant observations and in-depth interviews with eight selected informants. The results of the study show that self-disclosure carried out by students reflects four areas in the Johari Window theory, namely open, blind, hidden, and unknown, with the form of disclosure in the form of daily activities, outpouring of feelings, and emotional symbols such as quotes or songs. The positive impacts felt include increased self-understanding, emotional relief, and social support from peers. However, there are also negative impacts, such as social rejection and intrapersonal difficulties due to unmet expectations. This study concludes that Instagram Stories are an important expression space for students in the process of identity formation and emotional management in the digital era. Therefore, digital literacy and assistance from the school and family environment are needed so that adolescents can use social media healthily and responsibly.